Effect of calcination pretreatment on mechanical properties of alkali-activated artificial stone incorporating Yellow River silt. (1st September 2022) - Jiang, Sheng; Xu, Jinxia; Song, Yingbin; Gong, Wenjie; Wang, Liming; Yu, Zhihao; Wang, Guolong
Abstract: The resource utilization of the Yellow River silt is one of the key issues for the protection and management of the Yellow River in China. One of the effective methods for this goal is to prepare artificial stones using the Yellow River silt as the main raw materials. The purpose of this study is to explore the effect of calcination pretreatment on the mechanical properties of artificial stone incorporating Yellow River silt. The artificial stone was fabricated via the alkali-activation and pressure-forming method. The compressive strength and splitting tensile strength of fabricated artificial stone specimens with different alkali dosages, fly ash contents and curing ages were measured. The microstructures of alkali-activated artificial stone specimens were observed by field emission scanning electron microscopy (FESEM), energy-dispersive X-ray spectrum (EDS), X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR) and thermogravimetric analysis (TGA). The results show that the mechanical properties of the artificial stone incorporating Yellow River silt can be improved obviously by calcination pretreatment. Moreover, it can be found that alkali dosages, fly ash contents and curing ages play important roles in the level of improvement on the mechanical properties. The highest compressive strength of the artificial stones at 90 days is 16.6 MPa, and the corresponding splitting tensile strength is 1.4 MPa. The main reason for the increase of strength is that calcination pretreatment facilitates the production of alkali-activated products, that is, hydration calcium silicate (C–S–H) gels. These results suggest the possibility of using calcinated Yellow River silt as reliable and economical building materials in a wide range of construction engineering applications, especially in river slope protection, flood control and other projects. Graphical abstract: Image 1 Highlights: Calcinated Yellow River silt was used as raw materials of artificial stone. The most appropriate dosage of alkali was determined. The addition of fly ash increases the maximum compressive strength to 16.6Mpa. The main alkali-activation product is hydrated calcium silicate gel.